IN SILICO AND IN VIVO PHARMACOLOGICAL STUDIES OF CLOZAPINE AND D-AMINO ACID OXIDASE INHIBITOR FOR COGNITIVE ENHANCEMENT - S, Nithya; Ts, Shanmugarajan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: D-amino acid oxidase inhibitors (DAAOIs) are of particular focus for cognition study. Atypical antipsychotics are known DAAO inhibitors. The present examination was done to check out the binding affinity of atypical antipsychotics by docking toward the DAAO protein; in conclusion, the picked antipsychotic drug was checked for their cognition enhancing activity with scopolamine-induced amnesia. Methods: The crystal structure of DAAO was obtained from Protein Data Bank, the energy minimization was performed with CHARMM program, then active site prediction was made out using Ramachandran plot, and finally, docking examination was finished using Autodock 4.2 tool. For in vivo study, the mice were divided into three groups. Group I - vehicle (Saline) treated, Group II – saline +scopolamine (1 mg/kg, intraperitoneal [i.p]) treated, and Group III - clozapine (20 mg/kg, i.p) + scopolamine (1 mg/kg, i.p). Results: The Autodock examination shows significant binding affinity of - 5.22 for brexpiprazole and least or positive binding affinity of +1 for iloperidone. Clozapine with binding energy of - 2.87 was decided for completing the in vivo cognition study. The in vivo shows up that clozapine (20 mg/kg, i.p) exhibits a change in the impairment of spatial memory. Conclusion: The results recommend that the clozapine produces cognitive enhancement through both DAAOI and antipsychotic action. Clozapine has cognitive improvement potential, favoring its usage in reducing toxic impacts of scopolamine